2019
DOI: 10.1002/jms.4327
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the identification process of phenidate analogues in LC‐ESI‐MS/MS analysis: Information enhancement by derivatization with isobutyl chloroformate

Abstract: A new analytical technique for the structural elucidation of four representative phenidate analogues possessing a secondary amine residue, which leads to a major/single amine-representative fragment/product ion at m/z 84 both in their GC-EI-MS and LC-ESI-MS/MS spectra, making their identification ambiguous, was developed. The method is based on "in vial" chemical derivatization with isobutyl chloroformate in both aqueous and organic solutions, followed by liquid chromatography-electrospray ionization mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The resulting carbamate derivatives can yield different mass spectral fragmentation patterns and may provide additional structural information about the precursory secondary amine. The isobutyl formate derivatives of phenidate analogues provided the best results among chosen phenidate derivatives containing secondary amines, yielding unique product ions for improved structural information 18 . Preliminary results demonstrated that both isobutyl chloroformate and 2,2,2‐trichloro‐1,1‐dimethylethyl chloroformate (TCDMEDF) derivatizing agents were found to react efficiently with local anesthetic drugs that possess secondary amines, reducing their proton affinity.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting carbamate derivatives can yield different mass spectral fragmentation patterns and may provide additional structural information about the precursory secondary amine. The isobutyl formate derivatives of phenidate analogues provided the best results among chosen phenidate derivatives containing secondary amines, yielding unique product ions for improved structural information 18 . Preliminary results demonstrated that both isobutyl chloroformate and 2,2,2‐trichloro‐1,1‐dimethylethyl chloroformate (TCDMEDF) derivatizing agents were found to react efficiently with local anesthetic drugs that possess secondary amines, reducing their proton affinity.…”
Section: Resultsmentioning
confidence: 99%
“…20 Recently, we demonstrated how derivatization of tertiary and secondary amines can be used not only for sensitivity enhancement but also for the structural elucidation of several illicit drugs, pharmaceuticals, and proline-based dipeptides. [21][22][23][24][25] In the present study, we investigated the fragmentation behaviors of applied to the structural elucidation of a variety of dipeptides even in a complex matrix such as urine. To the best of our knowledge, this is the first report on the use of sodium adduct ions [M + Na] + and derivatization as an attractive approach to solving a problem related to the structural elucidation of dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical derivatization that allows sensitivity enhancement for G‐type nerve agents in various matrices was reported by Weissberg et al, 12–14 Blanca et al, 15 Madmon and Weissberg, 16 and Mach et al 17 employing 2‐[(dimethylamino)methyl]phenol (2‐DMAMP). In recent years, we have demonstrated how derivatization can be employed not only for sensitivity enhancement, but also for the structural elucidation of several illicit drugs, pharmaceuticals and other related compounds 18–22 . This study aims to develop a facile and easy technique for the structural elucidation of V‐type nerve agents based on chemical derivatization at trace levels.…”
Section: Introductionmentioning
confidence: 99%